A Long-Term Challenge – Enabling the Uptake of Advanced MBT Technologies in Eastern European Countries - Hornsby, K.; Benesova, L.; Zimová, M. (Journal of Environmental Accounting and Management, 2026)
This study considers the case of Czech Republic (CR), as a relatively new EU member state, looking at opportunities and challenges enabling this country to make the step-wise transition from the current dependence on fossil fuels (for energy production), incineration (for a fast way to deal with waste), and landfilling (as a cheap option for disposal) to one which reflects current concerns about climate change and moves towards a more circular resource saving economy. Part of the facilitation towards improvements in structures and processes in CR is to consider innovative developments especially in the area of treatment and recycling of municipal solid waste (MSW) based on mechanical biological treatment (MBT) technologies, as well as lessons learnt from other more advanced EU countries in waste management structures. An appropriate response to the climate change concerns has been the revised targets in reducing landfilling and increasing renewable energy sources towards a more sustainable energy use and waste management. In spite of the fact that the EU has issued key pieces of waste management and renewable energy Directives, compliance with diversion targets away from landfilling and renewable energy quotas are still considered too ambitious and far out of the reach of many Eastern European countries. This research holistically focuses on the MARSS 1 technology and its potential application and stakeholder acceptance in CR. MARSS is one-of-a-kind proven technology to remove and stabilise the biogenic fraction of MSW, to prevent landfilling and yield a refined biomass fuel for combined heat and power (CHP) production. Results from this study indicate that the MARSS technology has a higher potential in helping CR’s obligations to reduce the landfilling of organic material reduce CO2 emissions so complying with Annual Emission Agreements (AEA), as well as with adopted EU legislation in waste management, renewable energy and the circular economy. Based on the interviews carried out with key stakeholder groups, there are some positive indications that MBT plus MARSS could be an option, but it needs more time for development and implementation of new national legislation and an improvement in the markets to encourage confidence in the investment communities.